Reconfigurable planar inverted-F antenna for radio frequency identification tag and global positioning system applications - Assiya Amri; Tomader Mazri (Universitas Ahmad Dahlan, 2022)
This paper presents the design of a reconfigurable planar inverted-F antenna (PIFA). The proposed antenna is designed and optimized to operate in two frequency bands. 2.4 GHz allocated to the industrial, scientific and medical (ISM) band for the identification of a set of vehicules within a given area, and 1.575 GHz allocated to the global positioning system (GPS) band to locate them outside. The ISM band is used for microwave frequencies for active radio frequency identification (RFID) tag, which is associated with the object to be identified. This antenna consists of two radiating elements connected by a positive-intrinsic-negative (PIN) diode to obtain the frequency reconfigurability. The first radiating element is connected to the ground plane by a shorting pin and excited by a 50 Ω coaxial feed line. Its total size is 30 mm × 50 mm × 7 mm. The substrate used is FR4 with constant dielectric relativity of 4.4 and a height of 1.6 mm. Computer simulation technology microwave studio (CST MWS) software is used to simulate and optimize the proposed reconfigurable PIFA antenna.